THE IMAGE OF RUSSIA IN THE MINDS OF THE STUDENT YOUTH OF THE CRIMEA AND SEVASTOPOL: THE RESULTS OF A SOCIOLOGICAL SURVEY - O. V. Yarmak; A. M. Kanakh; V. E. Arkhipenko (Дискурс)
The study of the image of Russia in the minds of the youth of the Crimea and Sevastopol is extremely relevant in connection with the integration processes taking place on the peninsula. This issue becomes particularly relevant, since the existing image of Russia among young Crimean and Sevastopol people was formed in various social environments. The article presents some results of monitoring sociological research, which demonstrate the process of forming the image of Russia among the Crimean youth, and also describes the factors that influence this process. In particular, the impact of the understanding of the geopolitical status of the modern Russian state, the economic problems in the Republic of Crimea and the city of federal significance of Sevastopol, the level of political tension on the peninsula, the general socio-cultural background in which the young man lives are determined by the Crimean youth.